A child's world infancy through adolescence - Papalia, Diane E. (McGraw-Hill, 2006)
This fully-revised tenth edition continues to provide the extensive cross-cultural and multicultural coverage, the innovative pedagogical learning system, and the balance between research and real-life applications that have made A Child's World a favorite of both students and professors. In the warmly-written and engaging style that has become their hallmark, Papalia, Olds, and Feldman continue to provide a chronological view of child development; the new edition expands the coverage of cultural and historical influences on development, highlights the latest research, and introduces the LifeMap student CD-ROM.